Pengaruh Penggunaan Media Pembelajaran Flipchart terhadap Hasil Belajar Kognitif Siswa Kelas X SMA Negeri 24 Maluku Tengah : (The Effect of Using Flipchart Learning Media on Cognitive Learning Outcomes of Class X Students of SMA Negeri 24 Maluku Tengah) - Calvin Talakua; Febiayu Aloatuan (BIODIK, 2021)
The accuracy of using the media indirectly will stimulate students to take part in these lessons so that it will affect the good and bad results of student learning. The research design used Two Group Randomized Subjeck Posttest Only, by selecting two classes, namely the experimental class group and the control class group. The experimental class group used Flipchart learning media while the control class used conventional learning models. The same test was given to both classes, namely at the end of the lesson (posttest). From the results obtained, it is known that the cognitive learning outcomes of students using flipchart learning media are much better than students who use conventional learning models. This can be seen from the average score of the experimental class which is much higher than the control class, which is 80.44, while the control class is 58.93. From the results of hypothesis testing, it shows that tcount = 4.26 and ttable = 1.67 at the significant level α = 0.05 with degrees of freedom dk = (34+ 34-2). Based on the criteria for the hypothesis accept H0 if tcount <ttable with degrees of freedom dk = (n_1 + n_ (2) - 2) with a significant level α = 5% for other t values ​​H0 is rejected. Judging from the results of the calculation, it is known that the value of tcount> ttable. So that H_ (0) is rejected and H1 is accepted, which means that there is an effect of Flipchart learning media on cognitive learning outcomes of class X students of SMA Negeri 24 Maluku Tengah. Abstrak. Ketepatan penggunaan media secara tidak langsung akan menimbulkan rangsangan dari diri siswa untuk mengikuti pelajaran tersebut sehingga akan mempengaruhi baik buruknya hasil belajar siswa. Desain  penelitian  ini  menggunakan Two Group Randomized  Subjeck Posttest Only, dengan  memilih  dua  kelas  yaitu  kelompok  kelas  eksperimen dan kelompok  kelas  kontrol.  Kelompok  kelas  eksperimen  menggunakan  media pembelajaran Flipchart  sedangkan  kelas  kontrol  menggunakan  model  pembelajaran  konvensional. Tes  yang  sama  diberikan  pada  kedua  kelas  yaitu  pada  akhir  pembelajaran ( postes). Dari  hasil  yang didapat  diketahui hasil belajar kognitif siswa  yang  menggunakan  media pembelajaran Flipchart jauh  lebih  baik  daripada  siswa  yang  menggunakan  model  pembelajaran  konvensional.  Hal  ini  dilihat  dari  rata-rata  skor  kelas  eksperimen  yang  jauh  lebih  tinggi  dari  kelas  kontrol  yaitu  80.44  sedangkan  kelas  kontrol  58,93. Dari  hasil  pengujian  hipotesis  menunjukan  bahwa  thitung   = 4.26   ttabel  =  1.67  pada  taraf  singnifikan   =  0,05  dengan  derajat  kebebasan  dk = (34+ 34 - 2 ).  Berdasarkan  kriteria  hipotesis  terima   H0 jika  thitung < ttabel  dengan  derajat  kebebasan  dk = (  + - 2 )  dengan  taraf  signifikan   = 5% untuk  nilai t  lainnya  H0  ditolak.  Dilihat  dari  hasil  perhitungan  yang  didapat  diketahui  nilai  thitung  ttabel  Sehingga    demikian  ditolak  dan  H1  diterima  yang    artinya  bahwa  ada  pengaruh  media pembelajaran Flipchart terhadap  hasil belajar kognitif siswa kleas X SMA Negeri 24 Maluku Tengah.